About the Cover Image. (1st September 2020) - Allan, Jonathan A.; Haywood, Chris; Karioris, Frank G.
Abstract : On the cover of this issue, we have another image from the Wellcome Collection. This image by ABIA (Associação Brasileira Interdisciplinar de AIDS/Grupo) is a not-for-profit organization mobilized in response to the emergence of HIV/AIDS in the 1980's. The image is a reworking of the "Creation of Adam" by Michelangelo and was used as part of HIV/AIDS prevention advertising campaign.